Korean translation of idiomatic expressions hANjA SON-O - Sabitova, S. (Journal of Oriental Studies, 2016)
the article discusses Koreanidioms hanja son-o, their role and position in the lexical-phraseological system of language. the author concluded that the main difficulties in translation of phraseological units are stylistic undifferentiated and polysemy.